Natural history and clinical factors associated with persistence in pediatric lentil allergy - Konstantinos Miliordos; Triga Maria (Allergologia et Immunopathologia, 2026)
Background: Lentil is a widely consumed staple in Mediterranean countries and a significant cause of IgE-mediated legume allergy in children. Data on its natural history and the clinical factors associated with persistence remain limited. Methods: We retrospectively analyzed 62 children with confirmed lentil allergy who were followed at a tertiary pediatric allergy unit in Greece. Clinical manifestations, atopic comorbidities, food sensitization, lentil-specific IgE (sIgE), and Prick-to-Prick Test (PPT) wheal diameters were recorded. Tolerance was defined as a negative hospital-based oral food challenge. Primary prognostic analyses were restricted to children with OFC-confirmed outcomes. Results: The median age at diagnosis was 4 years, and 46/62 children (74.2%) were male. Cutaneous reactions were the most common presentation (40/62, 64.5%), while 22/62 children (35.5%) experienced anaphylaxis. During follow-up, 49/62 children underwent OFC; 17/49 (34.7%) were tolerant, whereas 32/49 (65.3%) had persistent allergy. Among OFC-confirmed patients, tolerant children had lower lentil sIgE levels than children with persistent allergy (median 1.40 vs. 17.95 kU/L, p < 0.001) and smaller PPT wheal diameters (median 5 vs. 7 mm, p < 0.001). Lentil sIgE showed high discriminative ability for persistence (AUC 0.906, 95% CI 0.825–0.988), with a Youden-derived threshold of 9.95 kU/L. PPT showed good discriminative performance (AUC 0.794, 95% CI 0.660–0.929), with a threshold of 5.5 mm. Anaphylaxis and polysensitization were associated with higher odds of persistence but did not reach statistical significance. Conclusions: Lentil allergy was frequently persistent in this cohort. Among OFC-confirmed children, higher lentil sIgE levels and larger PPT wheal diameters were the most robust markers associated with persistence and may support prognostic counseling, as well as the timing of re-evaluation and supervised reintroduction challenges.